CONCEPT HISAB IN ISLAMIC ACCOUNTIZATION BASED ON ISLAMIC EPISTEMOLOGY ANALYSIS - Norazita Marina Abdul Aziz; Dr. Fadzila Azni Ahmad (Journal of Islamic, Social, Economics and Development, 2017)
Islamic accounting refers to calculations, reckoning and arrangements based on muamalat affairs. The basis for Islamic accounting refers to a broad transaction covering all transactions recording financial and non-financial transactions and calculating the balance of receipts, payments and profits that should be distributed to the persons entitled. To clarify Islamic accounting profession in retrospect, it is necessary to first look at the foundations that form the philosophy of Islam based on the core of Islamic philosophy that is epistemology. Based on Islamic theoretical knowledge, Islamic epistemology is aimed at the truth of the knowledge based on the pursuit of Allah obtained through the Quran, and the Hadith ie the words, deeds and conversations of the Prophet (peace and blessings of Allaah be upon him) narrated from Sahih Sahih. The methodology of the study uses grounded theoretical studies based on the search for in-depth and detailed information. The scope of the study involves an in-depth examination of the major sources for the exploration of Islamic accounting related knowledge. Classification of concepts, categories, themes and patents is derived from grounded theory analysis. The details and depth of information on Islamic accounting are formed to answer the research questions. The findings of the study found that Islamic accounting is an important basis in recording accounting related transactions and Islamic transactions such as zakat and waqf. Zakat and waqf accounting involves transactions to record basic procedures based on Islamic transactions. As such, Islamic accounting should be established through the core of Islamic philosophy that involves Islamic tasawur, epistemology, ontology and Islamic axiology. From a transparent study through the core of the Islamic philosophy, a form of Islamic accounting concept has been established. The formation of Islamic accounting concepts was formed through the principles, features and elements based on the core of Islamic philosophy.